Teaching medical statistics to undergraduate medical students: what is taught and what is really useful for a medical professional? A report of the Education Committee of the Italian Society of Medical Statistics and Clinical Epidemiology (SISMEC) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: There is a large heterogeneity among the courses of medical statistics in Italian Medical Schools. Aims: (1) To describe issues that are dealt with in the statistics undergraduate medical courses in Italian medical Schools. (2) To investigate which methodological topics are deemed as more useful for the education of undergraduate medical students by clinical teachers. Methods: (1) An online questionnaire, covering the qualifying teaching issues of medical statistics, was sent to all academic biostatisticians, asking what they were teaching to undergraduate medical students. The reference year was 2015-2016. Undergraduate medical courses were the statistical units. (2) A second survey involved teachers of other medical disciplines with institutional roles, asking to score the usefulness for medical education of a number of topics concerning medical statistics, on a 5-point Likert scale. Only descriptive analyses were performed. Results: Fifty-two (96%) case report forms (CRF) were returned from teachers of medical statistics. Most statistical and epidemiological topics were taught except comparison of >2 groups, impact of biases and standardization of rates. Conversely, issues of clinical epidemiology were neglected in about half of degree courses. Thirty-three (31%) CRFs were returned from clinical teachers. The percentage of issues deemed very useful or essential ranged from 57% to 94%, with higher scores for those referring to critical assessment of the literature. Conclusions: More extensive coverage of clinical epidemiology issues is needed to meet the demand of physicians, as responsible consumers of quantitative research. As biostatisticians we should operate to increase the homogeneity of medical statistics teaching in medical undergraduates’ education